4.3 mũ x + 1 = (-2)+38
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a) \(4^{x+2}+4^x=68\)
\(\Rightarrow4^x\cdot\left(4^2+1\right)=68\)
\(\Rightarrow4^x\cdot17=68\)
\(\Rightarrow4^x=\dfrac{68}{17}\)
\(\Rightarrow4^x=4\)
\(\Rightarrow4^x=4^1\)
\(\Rightarrow x=1\)
b) \(5\cdot2^{x+4}-3\cdot2^x=308\)
\(\Rightarrow2^x\cdot\left(5\cdot2^4-3\right)=308\)
\(\Rightarrow2^x\cdot\left(5\cdot16-3\right)=308\)
\(\Rightarrow2^x\cdot77=308\)
\(\Rightarrow2^x=\dfrac{308}{77}\)
\(\Rightarrow2^x=4\)
\(\Rightarrow2^x=2^2\)
\(\Rightarrow x=2\)
c) \(4\cdot3^{x+1}+7\cdot3^x=513\)
\(\Rightarrow3^x\cdot\left(4\cdot3+7\right)=513\)
\(\Rightarrow3^x\cdot19=513\)
\(\Rightarrow3^x=\dfrac{513}{19}\)
\(\Rightarrow3^x=27\)
\(\Rightarrow3^x=3^3\)
\(\Rightarrow x=3\)
d) \(5^{x+4}-5^x=3120\)
\(\Rightarrow5^x\cdot\left(5^4-1\right)=3120\)
\(\Rightarrow5^x\cdot\left(625-1\right)=3120\)
\(\Rightarrow5^x\cdot624=3120\)
\(\Rightarrow5^x\cdot\dfrac{3120}{624}\)
\(\Rightarrow5^x=5\)
\(\Rightarrow5^x=5^1\)
\(\Rightarrow x=1\)
f) \(3\cdot4^{2x+1}-16^x=2816\)
\(\Rightarrow3\cdot4^{2x+1}-\left(4^2\right)^x=2816\)
\(\Rightarrow3\cdot4^{2x+1}-4^{2x}=2816\)
\(\Rightarrow4^{2x}\cdot\left(3\cdot4-1\right)=2816\)
\(\Rightarrow4^{2x}\cdot11=2816\)
\(\Rightarrow4^{2x}=\dfrac{2816}{11}\)
\(\Rightarrow4^{2x}=256\)
\(\Rightarrow\left(2^2\right)^{2x}=2^8\)
\(\Rightarrow2^{4x}=2^8\)
\(\Rightarrow4x=8\)
\(\Rightarrow x=2\)
Bài 2:
\(2^x+124=5^y\)
\(\Rightarrow5^y-2^x=124\)
\(\Rightarrow5^y-2^x=125-1\)
\(\Rightarrow\left\{{}\begin{matrix}5^y=125\\2^x=1\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}5^y=5^3\\2^x=2^0\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}y=3\\x=0\end{matrix}\right.\)
Vậy: ....
\(3^x+4\cdot3^{x-2}=333\)
\(\Rightarrow3^{x-2+2}+4\cdot3^{x-2}=333\)
\(\Rightarrow3^{x-2}\cdot\left(3^2+4\right)=333\)
\(\Rightarrow3^{x+2}\cdot\left(9+4\right)=333\)
\(\Rightarrow3^{x+2}\cdot13=333\)
\(\Rightarrow3^{x+2}=333:13\)
\(\Rightarrow3^{x+2}=\dfrac{333}{13}\)
Không có x nào thỏa mãn
⇒ x ∈ ∅
Bài 3 :
a) 4.(x-5) - 2 3=24.3
4x-20-8=48
4x=76
x=19
b) 4.x3+15=271
4.x3=256
x3=64
=> x=4
c) ( 2x-3)2= 169
=> 2x-3= 13
2x=16
x=8
Chúc bạn học tốt !
4*(x-5) - 2^3 = 2^4*3
4*(x-5) - 8 = 16*3
4*(x-5) - 8 = 48
4*(x-5) = 48 + 8
4*(x-5) = 56
x- 5 = 56 : 4
x - 5 = 14
x = 14 + 5
x = 19
\(1,a,A=\frac{356^2-144^2}{256^2-244^2}=\frac{\left(356-144\right)\left(356+144\right)}{\left(256-244\right)\left(256+244\right)}=\frac{212.500}{12.500}\)
\(A=\frac{212}{12}=\frac{53}{3}\)
\(b,B=253^2+94.253+47^2\)
\(B=\left(253+47\right)^2=300^2=90000\)
Bài 2
\(a,x^2-16x=-64\)
\(x^2-16x+64=0\)
\(\left(x-8\right)^2=0\)
\(x=8\)
\(b,\left(x+2\right)^2+4\left(x+2\right)+2=0\)
\(x^2+4x+4+4x+8+2=0\)
\(x^2+8x+14=0\)
\(\sqrt{\Delta}=\sqrt{\left(8^2\right)-\left(4.1.14\right)}=2\sqrt{3}\)
\(x_1=\frac{2\sqrt{3}-8}{2}=\sqrt{3}-4\)
\(x_2=\frac{-2\sqrt{3}-8}{2}=-\sqrt{3}-4\)
\(\left(3^7:3^3+4\cdot3^2\right)\cdot3-2^2\cdot2^3\)
\(=\left(3^4+4\cdot9\right)\cdot3-2^5\)
\(=117\cdot3-32\)
\(=351-32=319\)
\(=\left(3^4+4.3^2\right).3-2^2.2^3\\ =\left(81+4.9\right).3-2^2.2^3\\ =117.3-2^5\\ =351-2^5=319\)
82 : 4.3 +2.32
= 64:4.3 + 2.9
= 16 . 3 + 18
= 48 + 18
= 66